Developing a flipbook on environmental change topics to enhance students’ conceptual understanding of sustainable living - Miftah Nur Hanifah Rida; Umi Fatmawati; Puguh Karyanto; Lilis Kusumawati (University of Muhammadiyah Malang, 2025)
Sustainable living is a concept that refers to minimizing negative impacts on the surrounding environment. This research aims to develop an e-module flipbook on environmental change topic to increase insight into the concept of sustainable living. This R&D research using the modified ADDIE approach. The stage of this research consists of analysis, design, development, and implementation. Data collection used a needs analysis questionnaire either for the teachers or the students, an expert validation questionnaire (content and media), teacher assessments, and student responses. The data analysis techniques used are qualitative and quantitative. The qualitative analysis is based form the analysis data while the quantitative based on the module validation and practicality. The trial use was conducted in tenth class of Senior High School (SSHS) 2 of Karanganyar. The results: shows that (1) the characteristics of the flipbook e-module developed are equipped with interactive features, such as inserting images and videos using the platform Heyzine. (2) The results of the e-module validation test on validator 1 were 94.37% with very good criteria, while those from validator 2 were 94.37% with very good criteria. (3) The average percentage obtained from the results of the practicality test by Biology subject teachers is 75% and the validity criteria are practical with information that can be used with minor revisions. (4) The percentage of scores obtained from student responses or feedback is 88.99% with very good criteria. Based on the result of this research, this e-module is feasible as a learning media that teaches the concept of a sustainable living in environmental change topics.